Pengaruh Tingkat Kemiskinan terhadap Indeks Pembangunan Manusia di Provinisi Kalimantan Selatan Tahun 2015-2019 - Rizki, Muhammad Adam; Pahlevi, Khairi (PPJP ULM, 2023)
The research objective was to determine how much influence the poverty rate has on the Human Development Index in the Regency / City of the Province of South Kalimantan in 2015-2019. The data used is secondary data from the Central Statistics Agency of South Kalimantan Province. Secondary data used is panel data for 2015-2019 according to regencies / cities of Province South Kalimantan. Data analysis used panel data. The result of the research shows that simultaneously variable X (Poverty Level) affects variable Y (Human Development Index). Then partially, the poverty rate has a positive effect on the Human Development Index. With a regression coefficient of 7,709.